2021
DOI: 10.1186/s12052-021-00142-2
|View full text |Cite|
|
Sign up to set email alerts
|

Development and validation of a framework for the assessment of school curricula on the presence of evolutionary concepts (FACE)

Abstract: Evolution is a key concept of biology, fundamental to understand the world and address important societal problems, but research studies show that it is still not widely understood and accepted. Several factors are known to influence evolution acceptance and understanding, but little information is available regarding the impacts of the curriculum on these aspects. Very few curricula have been examined to assess the coverage of biological evolution. The available studies do not allow comparative analyses, due … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 87 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…In evolution, concepts that are abstract or counterintuitive include the difficulty to conceive of the spatial and temporal scales over which evolution occurs, probability and randomness [38,39]. In addition, understanding evolution requires linking a number of complex concepts and misconceptions about any one of them will impact the understanding of the others [40].…”
Section: (A) Misconceptions About Evolutionmentioning
confidence: 99%
“…In evolution, concepts that are abstract or counterintuitive include the difficulty to conceive of the spatial and temporal scales over which evolution occurs, probability and randomness [38,39]. In addition, understanding evolution requires linking a number of complex concepts and misconceptions about any one of them will impact the understanding of the others [40].…”
Section: (A) Misconceptions About Evolutionmentioning
confidence: 99%
“…The experiential content will be in a sequence of hands-on real-world project scenarios. Sá-Pinto et al, [49] assert learning goals and skills required are aligned and developed as part of the curriculum and some goals and skills are considered more important than others leading to variations. We hope to utilize real-world data sets and plan to develop the projects on commercial public cloud providers to give our learners a real-world experience.…”
Section: Course Designmentioning
confidence: 99%
“…In a systematic literature review conducted by Bruckermann et al (2020), aimed at identifying which precursory concepts in evolution early childhood and primary school children already possess or develop after an educational intervention, the authors found that even children aged up to seven years are able to understand the basic mechanisms of the core concepts in evolution, such as variation, inheritance and natural selection. Grether (2021) used lesson plans with active learning activities to teach specific evolutionary learning objectives (fossils, vestigial traits, common ancestry, heritability, natural selection and evolutionary time) to primary school students (grades [3][4][5]. This author reports a substantial improvement in the students' understanding of evolutionary concepts after engaging in these activities.…”
Section: Introductionmentioning
confidence: 99%